Accounting Information System Analysis on Credit Sales: Analisis Sistem Informasi Akuntansi pada Penjualan Kredit - Hayat, Kumala; Nasution, Yenni Samri Julianti; Nurwani, Nurwani (Indonesian Journal of Innovation Studies, 2025)
General Background: Credit sales are a key strategy in the automotive industry to boost sales volume, yet they pose significant challenges in transaction recording and receivables management. Specific Background: PT. Aksara Motor Medan still relies on a semi-manual accounting information system (AIS) for credit sales, leading to delays in reporting and increased credit risk. Knowledge Gap: Few studies have comprehensively examined the link between semi-manual systems and the rise of bad debts in mid-sized automotive companies. Aims: This study aims to analyze the effectiveness of AIS in supporting accurate recording, reporting, and control of credit sales at PT. Aksara Motor Medan. Results: Findings show that the system is suboptimal, with delayed data updates, weak internal controls, and the absence of an automated reminder system for delinquent customers. Novelty: The study proposes the integration of AIS with a risk-based assessment model using the 5C approach and the COSO framework to strengthen control and risk management. Implications: Full digitalization, structured staff training, automated notifications, and data-driven credit evaluation are recommended to improve operational efficiency and minimize bad debt risks.Highlight : The system is semi-manual, causing reporting delays and credit risk. Arrears rose from 15% to 23.8% in six months. Full digitalization and 5C-based risk analysis are recommended. Keywords : Accounting System, Credit Sales, Bad Debts, Internal Control, Aksara Motor